Ответы и объяснения

  • AlbuRin
  • светило науки
2013-06-19T09:52:30+04:00

4^(x-1/2)-5*2^(x-1)+3=0

 

(4^x)/(4^1/2)-5*(2^x)/(2^1)  +  3  =0

 

(1/2)*4^x  -  (5/2)*2^x  +  3  =  0

 

Умножим  обе  части  уравнения  на  2  и 

 

заменим  4^x = 2^(2x) , пoлучим.

 

2^(2x) -5*2^x +6 = 0

 

Заменим  2^x=t,   2^(2x) = t^2 

 

t^2  -  5t  +6  =  0

 

По  теореме  Виета  t    =  2,     t    =  3

                                        1               2

 

1)     2^x = 2     x   = 1

                            1      

                           

2)    2^x  =  3    x  =  log  3

                            2           2